2014
DOI: 10.1016/j.amjcard.2014.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Percutaneous Coronary Intervention–Associated Acute Cerebrovascular Accident (from the 1998 to 2008 Nationwide Inpatient Sample Database)

Abstract: Acute cerebrovascular accident (CVA) after percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS) and coronary artery disease (CAD) is associated with high morbidity and mortality. Nationwide Inpatient Sample from 1998 to 2008 was utilized to identify 1,552,602 PCIs performed for ACS and CAD. We assessed temporal trends in the incidence, predictors and prognostic impact of CVA in a broad range of patients undergoing PCI. The overall incidence of CVA was 0.56% (95% confidence interval (CI), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
3
0
2
Order By: Relevance
“…Since the incidence rate of acute stroke after PCI is 0.56%, it can be suggested that our patient experienced an ischemic event of unilateral abducens. This can happen due to microembolism during PCI resulting in left lateral rectus palsy [ 11 ]. Moreover, the proposed mechanisms of it include the formation of blood clots within the catheter and arterial wall along with their displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Since the incidence rate of acute stroke after PCI is 0.56%, it can be suggested that our patient experienced an ischemic event of unilateral abducens. This can happen due to microembolism during PCI resulting in left lateral rectus palsy [ 11 ]. Moreover, the proposed mechanisms of it include the formation of blood clots within the catheter and arterial wall along with their displacement.…”
Section: Discussionmentioning
confidence: 99%
“…El ACV y el AIT son complicaciones temibles, con una incidencia reportada entre 0,07% y 1% (4)(5)(6)(7)(8)(9)(10)(11)(12) . La ICP incrementa 17 veces el riesgo de presentarlas dentro de las primeras 48 horas del procedimiento (13) .…”
Section: Introductionunclassified
“…Entre las primeras se destacan: edad avanzada, sexo femenino, diabetes mellitus (DM), hipertensión arterial (HTA), enfermedad renal crónica (ERC) o enfermedad cerebrovascular previa, y fracción de eyección del ventrículo izquierdo (FEVI) disminuida. En cuanto a las características del procedimiento, se asocian con mayor riesgo los procedimientos más largos, con mayor volumen de contraste, utilización de catéteres más rígidos y de mayor calibre, procedimientos de emergencia, trombectomía, ATC sobre puentes venosos o sobre lesiones más complejas y uso de balón de contrapulsación intraaórtico (BCIA) (2,(4)(5)(6)(7)10,11,(14)(15)(16)(17)(18) .…”
Section: Introductionunclassified
“…6,7 Risk factors for periprocedural stroke include known cerebrovascular disease, older age, coronary atherosclerosis, and intra-aortic balloon pump use. [1][2][3] A history of prior cerebrovascular event also increases the risk of intracerebral hemorrhage related to PCI. 8 Utilization of platelet aggregation antagonists in addition to aspirin at the time of PCI has significantly reduced periprocedural ischemic events and has been adopted as the standard of care.…”
mentioning
confidence: 99%
“…[1][2][3] The majority of periprocedural strokes are ischemic in nature, with an embolic pattern and often involving the middle cerebral artery. 4,5 Stroke during PCI is associated with a substantial increase in both inhospital and 30-day mortality.…”
mentioning
confidence: 99%